2020
DOI: 10.1007/s00167-020-06353-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted TKA leads to a better prosthesis alignment and a better joint line restoration as compared to conventional TKA: a prospective randomized controlled trial

Abstract: PurposeCorrect positioning and alignment of the prosthesis is a very important factor for durability of prosthesis and implant survival which is improved with the use of technology in total knee arthroplasty. However, the long‐term functional outcomes and survivorship are unclear. For this study, it was hypothesized that mechanical axis alignment of lower limb, post‐operative joint line restoration, femoral and tibial component alignment is more accurate with the new handheld semi‐active robotic‐assisted TKA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 37 publications
2
68
1
Order By: Relevance
“…Multiple robotic‐assisted systems, including Navio, Mako and Robodoc, have been clinically used for TKA. In this connection, it has been reported that robotic‐assisted TKA resulted in better joint line restoration and prosthesis alignment compared to conventional TKA 18 . Collins et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple robotic‐assisted systems, including Navio, Mako and Robodoc, have been clinically used for TKA. In this connection, it has been reported that robotic‐assisted TKA resulted in better joint line restoration and prosthesis alignment compared to conventional TKA 18 . Collins et al.…”
Section: Discussionmentioning
confidence: 96%
“…Computer navigation, three‐dimensional (3D)‐printed individualized prostheses and robotic‐assisted TKA methods have been introduced to surgery to increase implantation accuracy, soft tissue preservation and mechanical axis alignment 15–19 . The first robotic system in orthopedic surgery is Robodoc, which has been used for TKA and total hip arthroplasty since 1992 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] For example, Sires et al 26 -5 of 11 TKA system in obtaining preoperatively planned coronal alignment of final limb and bone resection. Vaidya et al 27 also demonstrated that robotic-assisted TKA system acquired a better joint line restoration and prosthesis alignment as compared to the conventional TKA.…”
Section: Discussionmentioning
confidence: 98%
“…Inappropriate bone resection and associated flexion/extension gaps can result in suboptimal TKA component positioning, leading to component malalignment [ 6 , 7 ]. Surgical error leading to failed TKA can be avoided [ 8 , 9 ], and therefore, focus has been placed on developing strategies to improve the accuracy of implant sizing and positioning to recreate the knee joint line and to appropriately balance soft tissue to achieve an accurate overall implant and lower limb alignment [ 10 , 11 ]. In this regard, robotic arm-assisted TKA (RA-TKA) has emerged as a reliable method to achieve accurate and precise lower limb alignment after TKA [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%